A Shift in Tissue Stiffness During Hippocampal Maturation Correlates to the Pattern of Neurogenesis and Composition of the Extracellular Matrix - Ryu, Youngjae; Iwashita, Misato; Lee, Wonyoung; Uchimura, Kenji; Kosodo, Yoichi (Frontiers in Aging Neuroscience, 2021)
Aging changes the mechanical properties of brain tissue, such as stiffness. It has been proposed that the maintenance and proliferation of neural stem cells (NSCs) are regulated in accordance with extracellular stiffness. Neurogenesis is observed in restricted niches, including the dentate gyrus (DG) of the hippocampus, throughout mammalian lifetimes. However, profiles of tissue stiffness in the DG in comparison with the activity of NSCs from the neonatal to the matured brain have rarely been addressed so far. Here, we first applied ultrasound-based shear-wave elasticity imaging in living animals to assess shear modulus as in vivo brain stiffness. To complement the assay, atomic force microscopy was utilized to determine the Young’s modulus in the hippocampus as region-specific stiffness in the brain slice. The results revealed that stiffness in the granule cell layer and the hilus, including the subgranular zone, increased during hippocampal maturation. We then quantified NSCs and immature neural cells in the DG with differentiation markers, and verified an overall decrease of NSCs and proliferative/immature neural cells along stages, showing that a specific profile is dependent on the subregion. Subsequently, we evaluated the amount of chondroitin sulfate proteoglycans (CSPGs), the major extracellular matrix (ECM) components in the premature brain by CS-56 immunoreactivity. We observed differential signal levels of CSPGs by hippocampal subregions, which became weaker during maturation. To address the contribution of the ECM in determining tissue stiffness, we manipulated the function of CSPGs by enzymatic digestion or supplementation with chondroitin sulfate, which resulted in an increase or decrease of stiffness in the DG, respectively. Our results illustrate that stiffness in the hippocampus shifts due to the composition of ECM, which may affect postnatal neurogenesis by altering the mechanical environment of the NSC niche.